Revitalize Hearing Skills with Advanced Speech Processing Technology - Nimah, Mamluatun; Imelda, Imelda; Batubara, Muhammad Hasyimsyah; Sidik, Jafar; Siminto, Siminto (Journal International of Lingua and Technology, 2024)
Revitalizing listening skills with advanced sound processing technology is an interesting concept, especially in today's digital era where technology is advancing rapidly. Listening skill is the ability to understand, analyze, and respond well to information conveyed through sound, and this is a key skill in various contexts, such as interpersonal communication, business, education, and others. Here are some ways revitalizing hearing skills with advanced sound processing technologies can be accomplished, Introduction to Sound Processing Technologies, It is important to understand what advanced sound processing technologies are. This includes using speech processing algorithms, speech recognition techniques, and even artificial intelligence (AI) to optimize speech understanding and interpretation. Hearing Skills Training Speech processing technology can be used in hearing skills training. For example, an application that can record, analyze and provide feedback on a person's hearing ability. Such applications can be used in the context of business education or training. Automatic Transcription and Translation, Voice processing technology can be used to convert conversations in foreign languages ??into text or translate voice content in real time. This can help someone understand a foreign language or content displayed in a language they are not familiar with. Improved Business Communications, In business, voice processing technology can be used to record, analyze and provide feedback on presentations, meetings or telephone conversations. This can help improve business communication skills. Providing Better Customer Service Many companies use voice processing technology to improve their customer service. Advanced voice interactive systems (IVR) can be used to route customer calls more efficiently and provide necessary information. Sentiment Understanding Advanced voice processing technology can be used to analyze sentiment in conversations or customer reviews. This can help companies understand the views and feelings of their customers. Educational Applications Speech processing technology can also be used in education to create more interactive teaching materials.